Famous : a novel [large type] - Crouch, Blake (Random House Large Print, 2025)
"Meet Lance. Thirty-eight years old. Works a meaningless job. Still lives above his parents' garage. By all accounts, a world-class loser. Save for one glaring exception: He has a million-dollar face. Lance has been mistaken eighty-seven times for the Oscar-winning movie star James Jansen, and for the last ten years, he's saved his money, studied Jansen's films, his moves, his idiosyncrasies-even the way he speaks. Now, after an unceremonious termination from his job, Lance has decided that the time has come to go after his dream of truly becoming Jansen. From New York's avant-garde, off-off Broadway scene to the glitter of Los Angeles, Lance embarks on a journey towards becoming James Jansen that will take him far closer to the star than even he had dreamed-and to far darker lengths than he could've possibly imagined." --